2003
DOI: 10.1002/j.1556-6978.2003.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Prepracticum Service‐Learning: Examining the Relationship With Counselor Self‐Efficacy and Anxiety

Abstract: Prepracticum service‐learning is an integral part of the curriculum for counselor education students at a large southwestern university. Service‐learning is accomplished by placing novice students in school or community agency settings to acquire early, practical, field‐based experience. Activities are more structured and supervised than in an internship or practicum. Analysis indicated that prepracticum service‐learning had a positive significant relationship with counselor self‐efficacy and a significant neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 16 publications
5
57
1
7
Order By: Relevance
“…The finding from Barbee, Scherer, and Combs (2003) of an inverse relationship between self-efficacy and anxiety is an interesting one that has received empirical support from other researchers (Bowman & Roberts, 1979;Friedlander, Keller, Peca-Baker, & Olk, 1986). According to Bandura, selfefficacy relates to one's ability to deal with stressful or anxiety-provoking situations; with increasing self-efficacy, one's belief that he or she can deal with anxiety/arousal also increases (Bandura, 1993).…”
Section: Self-efficacy and Affectmentioning
confidence: 81%
See 1 more Smart Citation
“…The finding from Barbee, Scherer, and Combs (2003) of an inverse relationship between self-efficacy and anxiety is an interesting one that has received empirical support from other researchers (Bowman & Roberts, 1979;Friedlander, Keller, Peca-Baker, & Olk, 1986). According to Bandura, selfefficacy relates to one's ability to deal with stressful or anxiety-provoking situations; with increasing self-efficacy, one's belief that he or she can deal with anxiety/arousal also increases (Bandura, 1993).…”
Section: Self-efficacy and Affectmentioning
confidence: 81%
“…Though the most widely used instruments are the COSE and CASES, Tang and colleagues (2004) found a positive relationship among course work, internship hours, and counseling-related work experience using a different measure of self-efficacy, the Self-Efficacy Inventory (Friedlander & Snyder, 1983). Barbee, Scherer, and Combs (2003) also found a positive relationship between counseling course work and counseling work experience but by using the Counselor Self-Efficacy Scale (Melchert, Hays, Wiljanen, & Kolocek, 1996). They also found a negative relationship between counselor self-efficacy and anxiety.…”
Section: Measuring Self-efficacy and Counselor Developmentmentioning
confidence: 99%
“…Field placement orientations can include a variety of supportive elements. Barbee, Scherer, and Combs (2003) suggested implementing pre-practicum servicelearning activities to prepare students for clinical experiences. A mentorship program aimed at developing relationships between students who are in later stages of field experience with students who are beginning practicum also may prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of service learning in counselor training have included variables such as multicultural competence (Burnett, Hamel, & Long, 2004), professional development (Jett & Delgado-Romero, 2009), counselor self-efficacy and anxiety (Barbee, Scherer, & Combs, 2003), and increased self-awareness and comfort working with unfamiliar clinical populations (Arnold & McMurtery, 2011). Briggs et al (2009) studied leadership directly and found that school counselor trainees developed leadership skills through both leadership training and participation as leaders in a week-long girls' leadership development camp.…”
Section: Leadership and Community-based Servicementioning
confidence: 99%